Family firm performance in times of crisis—new evidence from Germany - Svenja Jarchow; Christoph Kaserer; Henry Keppler (Eurasian Business Review, 2023)
Literature shows that founding-family control tends to positively impact firm performance and valuation. However, it is questioned whether this positive impact also persists in times of crisis or might even be reverted, as in such periods families could be focused on the survival of the firm even at the expense of long-term cash flows. By studying a large sample of listed German firms over the period 1998–2018, we document a significant outperformance of family firms in terms of ROA and (to a lesser extent) Tobin's Q during the crisis years 2008–2010 relative to their non-family counterparts. Moreover, this crisis resilience is more pronounced the stronger the family influence in terms of equity ownership. Outside the crisis period, there is only weak evidence for any outperformance. Digging deeper into this crisis effect, we find family firms to significantly reduce their leverage during the crisis. This, however, is not done at the expense of future cash flows, as we find weak evidence that family firms increase their capital expenditures as well as their employment relative to their non-family counterparts. Given that these results also hold in a dynamic panel system GMM approach and withstand a battery of robustness tests, we hope to add new evidence on the drivers of family firm performance.
Keywords: G01; G32; G34; G35; 650; Family firm performance; Agency theory; Ownership structure; Crisis management